Metaphor and Symbolism in The Song 'Supernova Love' By Ive and David Guetta - Istighfari, Tiara; Setiawan Djuharie, Otong; Andang Saehu (Jejak digital: Jurnal Ilmiah Multidisiplin, 2025)
This study examines how space-related symbols and comparisons are used in a song “Supernova Love” by the K-pop group IVE, featuring EDM (Electronic Dance Music) maker David Guetta. Through a semiotic approach, it reflect on how heavenly phenomena are metaphorically used to interpret lovesickness and human emotions. Results of this research suggest that the supernova metaphor– representative of a star that explodes and emits bright light– serves as a metaphorical cornerstone in the depiction of the strength and transient quality of romantic relationships. The study also fuses the hybridization of K-pop with global electronic music styles, as well as the singing of harmonies in languages other than the primary one, using them as a stimulus for mass listening and producing listening data that seeks to justify the download of lyrics.